Implant Restoration of Edentulous Jaws with 3D Software Planning, Guided Surgery, Immediate Loading, and CAD-CAM Full Arch Frameworks. (29th July 2013) - Meloni, Silvio Mario; De Riu, Giacomo; Pisano, Milena; Lolli, Francesco Maria; Deledda, Alessandro; Campus, Guglielmo; Tullio, Antonio
Abstract : Purpose . The aim of this study was to analyze the clinical and radiographic outcomes of 23 edentulous jaws treated with 3D software planning, guided surgery, and immediate loading and restored with CAD-CAM full arch frameworks. Materials and Methods . This work was designed as a prospective case series clinical study. Twenty patients have been consecutively rehabilitated with an immediately loaded implant supported fixed full prosthesis. A total of 120 fixtures supporting 23 bridges were placed. 117 out of 120 implants were immediately loaded. Outcome measures were implants survival, radiographic marginal bone levels and remodeling, soft tissue parameters, and complications. Results . 114 of 117 implants reached a 30 months follow-up, and no patients dropped out from the study. The cumulative survival rate was 97.7%; after 30 months, mean marginal bone level was 1.25 ± 0.31  mm, mean marginal bone remodeling value was 1 . 08 ± 0.34, mean PPD value was 2.84 ± 0.55  mm, and mean BOP value was 4% ± 2.8%. Only minor prosthetic complications were recorded. Conclusion . Within the limitations of this study, it can be concluded that computer-guided surgery and immediate loading seem to represent a viable option for the immediate rehabilitations of completely edentulous jaws with fixed implant supported restorations. This trial is registered with Clinicaltrials.gov NCT01866696 .